Comparison of maternal and fetal outcomes among patients undergoing cesarean section under general and spinal anesthesia: a randomized clinical trial - Saygı, Anıl İçel (2015)
CONTEXT AND OBJECTIVE: As the rates of cesarean births have increased, the type of cesarean anesthesia has gained importance. Here, we aimed to compare the effects of general and spinal anesthesia on maternal and fetal outcomes in term singleton cases undergoing elective cesarean section. DESIGN AND SETTING: Prospective randomized controlled clinical trial in a tertiary-level public hospital. METHODS: Our study was conducted on 100 patients who underwent cesarean section due to elective indications. The patients were randomly divided into general anesthesia (n = 50) and spinal anesthesia (n = 50) groups. The maternal pre and postoperative hematological results, intra and postoperative hemodynamic parameters and perinatal results were compared between the groups. RESULTS: Mean bowel sounds (P = 0.036) and gas discharge time (P = 0.049) were significantly greater and 24th hour hemoglobin difference values (P = 0.001) were higher in the general anesthesia group. The mean hematocrit and hemoglobin values at the 24th hour (P = 0.004 and P < 0.001, respectively), urine volume at the first postoperative hour (P < 0.001) and median Apgar score at the first minute (P < 0.0005) were significantly higher, and the time that elapsed until the first requirement for analgesia was significantly longer (P = 0.042), in the spinal anesthesia group. CONCLUSION: In elective cases, spinal anesthesia is superior to general anesthesia in terms of postoperative comfort. In pregnancies with a risk of fetal distress, it would be appropriate to prefer spinal anesthesia by taking the first minute Apgar score into account. CLINICAL TRIAL REGISTRY: NTR17990